Aerophytic cyanoprokaryotes from the Atlantic rainforest region of São Paulo State, Brazil: Chroococcales and Oscillatoriales - Branco, Luis Henrique Z. [UNESP]; Hoffmann, Lucien; Teixeira, Joana Pozzetti [UNESP]; Ferreira, Viviani [UNESP]; de Morais Filho, Jose Cesar [UNESP] (Adac-cryptogamie, 2009)
Because algae are primarily aquatic, it seems almost paradoxical that there Should exist a relatively diversified soil flora where aerophytic cyanoprokaryotes are especially abundant. However, there appear to be relatively few studies oil this topic. This paper aims to improve the taxonomic knowledge oil the chroococcalean and oscillatorialean cyanoprokaryote flora in tropical regions. Samples of cyanoprokaryotes were collected in the rainforest region of the São Paulo State, Brazil. Data oil cyanoprokaryote mass type and color, substratum type, air and mass temperature and humidity, pH and absolute and relative irradiance were collected. The study revealed the presence of 24 species belonging to the orders Chroococcales and Oscillatoriales (12 species each). Aphanothece (four species) was the most species-rich genus. Overall, taxonomic resolution at the species level based oil morphological and morphometric data can still be problematic.
Keywords: Aerophytic algae; Brazil; Chroococcales; Cyanobacteria; Cyanoprokaryota; Oscillatoriales; Taxonomy; tropical rainforest